Hispidulin Attenuates Cardiac Hypertrophy by Improving Mitochondrial Dysfunction - Wang, Yan; Xie, Zengshuo; Jiang, Nan; Wu, Zexuan; Xue, Ruicong; Dong, Bin; Fan, Wendong; Dai, Gang; Chen, Chen; Li, Jiayong; Chen, Hao; Ye, Zi; et al. (Frontiers in Cardiovascular Medicine, 2020)
Cardiac hypertrophy is a pathophysiological response to harmful stimuli. The continued presence of cardiac hypertrophy will ultimately develop into heart failure. The mitochondrion is the primary organelle of energy production, and its dysfunction plays a crucial role in the progressive development of heart failure from cardiac hypertrophy. Hispidulin, a natural flavonoid, has been substantiated to improve energy metabolism and inhibit oxidative stress. However, how hispidulin regulates cardiac hypertrophy and its underlying mechanism remains unknown. We found that hispidulin significantly inhibited pressure overload-induced cardiac hypertrophy and improved cardiac function in vivo and blocked phenylephrine (PE)-induced cardiomyocyte hypertrophy in vitro. We further proved that hispidulin remarkably improved mitochondrial function, manifested by increased electron transport chain (ETC) subunits expression, elevated ATP production, increased oxygen consumption rates (OCR), normalized mitochondrial morphology, and reduced oxidative stress. Furthermore, we discovered that Sirt1, a well-recognized regulator of mitochondrial function, might be a target of hispidulin, as evidenced by its upregulation after hispidulin treatment. Cotreatment with EX527 (a Sirt1-specific inhibitor) and hispidulin nearly completely abolished the antihypertrophic and protective effects of hispidulin on mitochondrial function, providing further evidence that Sirt1 could be the pivotal downstream effector of hispidulin in regulating cardiac hypertrophy.